SYNTHESIS AND CHARACTERIZATION OF LAYERED DOUBLE HYDROXIDE NANOSTRUCTURES AND THEIR APPLICATION IN THE REMOVAL OF Fe2+ AND Ca2+ IONS FROM OIL WELLS - Khansi, Ephraim E. Khansi; Anyama, Chinyere A.; Ayi, Ayi A.; Onwuka, Jude C. (Acta Scientiae et Intellectus, 2024)
Four new metal-aluminum layered double hydroxides (LDHs): Mg-Al(OH)2PO4 1, Mg-Al(OH)2PO4PF6 2, Ca-Al(OH)2SO4, 3 and Ca-Al(OH)2PO4PF6 4, were prepared by co-precipitation method followed by mild hydrothermal processing at 60 o C. Mg2+ and Ca2+ in solution with Al3+ was titrated with NaOH over 3-5 h to yield Mg-Al and Ca-Al layered double hydroxides, respectively, incorporating PO43-, PO43-PF6- and SO42- anions in the inter-lamellar spaces. The isolated compounds were characterized with the help of XRD, IR, SEM/EDAX and their ability to remove scale forming ions from aqueous system was studied with the help of Atomic Absorption Spectroscopy (AAS). The SEM micrographs of Mg-O-Al-OH and Ca-O-Al-OH layers intercalated with PO43- and / or [PO4PF6 ]4- anions are similar consisting of uniform nano- spheres with average size of 100 nm, while the M-O-Al-OH layer of compound 3, intercalated with SO42- anions consists of hexagonal nano-plate crystals. In the infrared spectra, the characteristic absorption band for water molecules was observed in all the compounds. The XRD pattern showed that d012 and d104 peaks of M-Al-PO4 LDHs corresponding to interplanar spacing of 3.4804 and 2.5504 Å respectively, shifted to higher 2θ values for M-Al-PO4PF6 system, which indicates a decrease in the interlamellar spacing as PF6 - was incorporated along with PO43- anion. The XRD pattern for Ca-Al-SO4 LDHs was quite different, showing the presence of low angle peaks at 2θ = 11.68 and 14.72o. The results of the column adsorption studies showed that there was a significant removal of Ca2+ by all the compounds under investigation with efficiency of 84 -99 %. Whereas compounds 1 and 2 removes Fe2+ effectively with efficiency of 98.73 and 99.77 %, respectively, compounds 3 and 4 were shown to have little or no effect. Keywords: Layered